CNTNAP2 stabilizes interneuron dendritic arbors through CASK. Issue 9 (September 2018) - Gao, Ruoqi; Piguel, Nicolas; Melendez-Zaidi, Alexandria; Martin-de-Saavedra, Maria; Yoon, Sehyoun; Forrest, Marc; Myczek, Kristoffer; Zhang, Gefei; Russell, Theron; Csernansky, John; Surmeier, D.; Penzes, Peter
Abstract Contactin associated protein-like 2 (CNTNAP2 ) has emerged as a prominent susceptibility gene implicated in multiple complex neurodevelopmental disorders, including autism spectrum disorders (ASD), intellectual disability (ID), and schizophrenia (SCZ). The presence of seizure comorbidity in many of these cases, as well as inhibitory neuron dysfunction inCntnap2 knockout (KO) mice, suggests CNTNAP2 may be crucial for proper inhibitory network function. However, underlying cellular mechanisms are unclear. Here we show that culturedCntnap2 KO mouse neurons exhibit an inhibitory neuron-specific simplification of the dendritic tree. These alterations can be replicated by acute knockdown of CNTNAP2 in mature wild-type (WT) neurons and are caused by faulty dendrite stabilization rather than outgrowth. Using structured illumination microscopy (SIM) and stimulated-emission depletion microscopy (STED), two super-resolution imaging techniques, we uncovered relationships between nanoscale CNTNAP2 protein localization and dendrite arborization patterns. Employing yeast two-hybrid screening, biochemical analysis, in situ proximity ligation assay (PLA), SIM, and phenotype rescue, we show that these effects are mediated at the membrane by the interaction of CNTNAP2's C-terminus with calcium/calmodulin-dependent serine protein kinase (CASK ), another ASD/ID risk gene. Finally, we show that adultCntnap2 KO mice have reduced interneuron dendritic length and branching in particular cortical regions, as well as decreased CASK levels in the cortical membrane fraction. Taken together, our data reveal an interneuron-specific mechanism for dendrite stabilization that may provide a cellular mechanism for inhibitory circuit dysfunction inCNTNAP2 -related disorders.